A validated LC-MS/MS method for studying the pharmacokinetic interaction of Immusante® and antiviral drugs in rats - Lakavalli Mohankumar Sharath Kumar, Mohammed Mukhram Azeemuddin, Tirumalai Ramanujam Tulasi, Madhavan Vijayakumar, Uddagiri Venkanna Babu, K Sreedhara Ranganath Pai (Journal of Applied Pharmaceutical Science, 2023)
A revisit through history reveals that viral outbreaks like smallpox, polio, measles, Ebola, severe acute respiratory syndrome, middle east respiratory syndrome, HIV, Dengue, and Hanta to the current pandemic COVID-19 have jeopardised millions of lives across the globe. Currently, there is no vaccine available for many viral diseases. Hence, we rely on anti-viral therapies that target various phases of viral replication. Patients across the world also consume herbal supplements to gain an effective therapeutic approach by enhancing the body’s innate immune mechanism and managing the side effects. Immunomodulators like Immusante®, a herbal formulation composed of Shanta (Prosopis glandulosa) and Lodhra (Symplocos racemose) proprietorship of “Himalaya Wellness Company” is commonly used as an adjuvant therapy along with anti-viral, anti-tubercular, and anti-cancer drugs to support the impaired immune system and increase the chance of long-term disease-free state by mitigating relapse. With a growing understanding of plant-based complementary or alternative medicine, it is necessary to assess the herb–drug interactions. The present study aims to establish a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) drug interaction model (in vivo) for real-time quantification of Acyclovir, Lamivudine, and Amantadine in rat plasma based on bioanalytical method validation guidelines recommended by USFDA. A sensitive LC-MS/MS method was developed and validated to assess the drug interaction studies and our results suggest that Immusante® may be used as an adjuvant along with these potent antiviral drugs as it does not possess any pharmacokinetic interactions.
Keywords: Antiviral drugs, drug-drug interactions, pharmacokinetics, immusante